The bio.tools registry of software tools and data resources for the life sciences - Ison, Jon; Ienasescu, Hans; Chmura, Piotr; Rydza, Emil; Ménager, Hervé; Kalaš, Matúš; Schwämmle, Veit; Grüning, Björn; Beard, Niall; Lopez, Rodrigo; Duvaud, Severine; Stockinger, Heinz; et al. (Genome biology, 2019)
Bioinformaticians and biologists rely increasingly upon workflows for the flexible utilization of the many life science tools that are needed to optimally convert data into knowledge. We outline a pan-European enterprise to provide a catalogue ( https://bio.tools ) of tools and databases that can be used in these workflows. bio.tools not only lists where to find resources, but also provides a wide variety of practical information.
Keywords: Software; Databases, Factual; software; biologické vědy; internet; databáze faktografické; Internet; Biological Science Disciplines